2019
DOI: 10.4067/s0718-18762019000100105
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Black Box of Shifting from Electronic Commerce to Mobile Commerce: The Case of Jordan

Abstract: Mobile computing and the wireless web are likely to become the next major business models following the era of electronic commerce. In particular, rapid growth and the advancement in mobile technologies indicate that mobile commerce (m-commerce) will be the dominant business model in the future. In developing countries, services in mobile commerce are in a phase of rapid growth, yet the relevant research is limited. Thus, to increase the adoption of m-commerce among consumers in developing countries such as Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…Removing items that fall outside this value helps to refine the dataset and reduce the probability of it affecting the outcome of the exploratory factor analysis. The result of the Skewness and Kurtosis statistical test for each construct was between +2 and −2 [76], showing that the responses regarding the study's constructs were normally distributed. Furthermore, the Cronbach's alpha shown in Table (2) indicate that all the constructs were above the acceptable level of 0.70 [77].…”
Section: A Exploratory Studymentioning
confidence: 97%
“…Removing items that fall outside this value helps to refine the dataset and reduce the probability of it affecting the outcome of the exploratory factor analysis. The result of the Skewness and Kurtosis statistical test for each construct was between +2 and −2 [76], showing that the responses regarding the study's constructs were normally distributed. Furthermore, the Cronbach's alpha shown in Table (2) indicate that all the constructs were above the acceptable level of 0.70 [77].…”
Section: A Exploratory Studymentioning
confidence: 97%
“…In the m-commerce context, inconsistencies in the results were observed according to the mcommerce context and the sample size. To illustrate this, EE has an effect on m-commerce, but this effect is weak (Yoon and Steege, 2013;Chantzaras et al, 2017;Sun and Chi, 2017;Hsu and Yeh, 2018;Al-Adwan et al, 2019). In contrast, many studies found that EE has a strong positive effect on m-commerce (Martins et al;Chantzaras et al, 2017;Sun and Chi, 2017;Hsu and Yeh, 2018).…”
Section: Effort Expectancymentioning
confidence: 99%
“…Trust can be transformed into loyalty, which will certainly drive the process of purchasing decision making [16,18,39]. In the digital environment, trust is referred to as "online trust" or "e-trust" and it has commonly been assumed that it is related to e-loyalty in the context e-commerce [13].…”
Section: E-trust Reputation E-satisfaction and E-loyaltymentioning
confidence: 99%